ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP DI TINJAU DARI RESILIENSI MATEMATIK - Hani Ismatillah Kurnia; Yani Royani; Heris Hendriana; Puji Nurfauziah (IKIP Siliwangi, 2018)
This research is a descriptive research with qualitative approach which aims to describe and analyze students' difficulties in completing the mathematical communication capability in review of mathematical resilience. The sample of research is the students of class VIII G SMP Negeri 2 Cisarua as many as 28 people. The instruments used are communication skill test, questionnaire of mathematical resilience and interview guidance. The result of data analysis showed that communication ability of students who have high resilience was able to solve the problem of mathematical communication skill well, as well as resilient students were able to complete the test of mathematical communication ability well, but the low resilience students were less precise in completing the test the ability of mathematical communication.